2001
DOI: 10.1080/13102818.2001.10819124
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Some Endogenous Plant Hormones During Induction of Somatic E Mbryogenesis in Common Bean (Phaseolus Vulgaris L.)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The number of embryos obtained was reduced if the concentration ratio of auxin: sucrose was high, or vice versa. In the study of somatic embryogenesis in Phaseolus vulgaris induced by 2,4-D, it was shown that there was an inverse relationship between 2,4-D concentration in the medium and endogenous IAA level in the globular structures (Dobrev et al, 2001). Using an immunocytochemical approach to visualize IAA it was shown in sunflower somatic embryos that an endogenous auxin pulse induced by the application of exogenous auxin is needed as one of the first signals inducing embryogenesis (Thomas et al, 2002).…”
Section: Embryogenesismentioning
confidence: 99%
“…The number of embryos obtained was reduced if the concentration ratio of auxin: sucrose was high, or vice versa. In the study of somatic embryogenesis in Phaseolus vulgaris induced by 2,4-D, it was shown that there was an inverse relationship between 2,4-D concentration in the medium and endogenous IAA level in the globular structures (Dobrev et al, 2001). Using an immunocytochemical approach to visualize IAA it was shown in sunflower somatic embryos that an endogenous auxin pulse induced by the application of exogenous auxin is needed as one of the first signals inducing embryogenesis (Thomas et al, 2002).…”
Section: Embryogenesismentioning
confidence: 99%